Sur les usages publics du secret : les archives du Service Secret Communiste Roumain - Andi Mihalache (L'Atelier du CRH)
This article focuses on the Securitate files as a political stake, but also as first rank sources for academic research, not from the current perspective of recent history, but from that of cultural history. In post-communist Romania, silence is the secret’s poor relative and confidentiality its respectable form. Ironically or not, we could state that in our country the secrets of communist repression are literally protected by law. The secret is an unbidden, illegitimate competence. In its ethics it does not matter what is good and what is bad, what is true and what is false. The main interest is what is said and what isn’t. The secret being a convention, a pact, the gesture of not saying seems to be more important than the thing unsaid. The inexpressible, the unsaying create relationships, social complicity, but also hierarchies, demarcations between those who hold a secret and those who do not know it or are afraid for this not to be divulged.